Pengaruh Sektor Produk Domestik Regional Bruto (Basis dan Non Basis) Terhadap Pertumbuhan Ekonomi dalam Perspektif Ekonomi Islam - Anggel Dwi Satria; Ridwansyah Ridwansyah; Ahmad Habibi (Jurnal Ilmiah Ekonomi Islam, 2023)
Based on Presidential Regulation Number 63 of 2020 concerning the Determination of Underdeveloped Regions for 2020-2024, the Pesisir Barat Regency is included in the underdeveloped category in Lampung Province. One of these lags can be seen from the community's economy. Economic growth is one indicator in measuring economic development in a region or country. According to data obtained from the BPS for Pesisir Barat Regency during the period 2013-2020, the economic growth of Pesisir Barat Regency tends to fluctuate. This growth cannot be separated from the role of each economic sector. Therefore, it is necessary to examine 17 economic sectors according to business fields to find out what economic sectors have the potential or advantages to become basic sectors and non-base sectors. The basic sector is the sector that forms the backbone of the local economy because it has a competitive advantage, and the non-base sector is the sector that supports local consumption needs. The formulation of the problem in this study is whether the basic and non-base sectors partially have a significant effect on economic growth in Pesisir Barat Regency? Does the base and non-base sectors simultaneously affect economic growth in Pesisir Barat Regency? And what is the view of Islamic Economics on the influence of the base and non-base sectors on economic growth in Pesisir Barat Regency? This study is a quantitative study with secondary data published by the Central Statistics Agency in the 2013-2020 observation period. The type of research is library research. The data analysis technique used is Location Quotient (LQ), Klassen Typology, and Multiple Linear Regression Analysis processed with the Eviews-9 program. Based on the results of data processing, it shows that the base sector variable has a positive and insignificant effect on economic growth in Pesisir Barat Regency. Then the non-base sector variable has a positive and insignificant effect on economic growth in Pesisir Barat Regency. And the base sector and non-base sector variables simultaneously have a positive and significant effect on economic growth in Pesisir Barat Regency, because the probability value is 0.002421 which means the prob value is less than (0.002421 < 0.05) so Ho is rejected, with an effect of 87.4 %. It can be concluded that the basic sector partially has a positive and insignificant effect on economic growth, as well as the non-base sector partially also has a positive and insignificant effect on economic growth. While the base sector and non-base sector simultaneously or together have a positive and significant influence. In this case, it means that if the base sector and non-base sector are increased, it will affect the economic growth in Pesisir Barat Regency to increase. In the view of Islamic economics that Allah SWT commands humans as caliphs on earth to utilize natural resources as they should by not prioritizing the interests of a few humans, but all creatures on earth. With this research, it is expected to be able to promote, maintain, utilize the basic sector and the non-base sector in accordance with Islamic teachings for the welfare of the community to achieve the goal of falah.